Fabrication of artificial defects using 3D printing for non-destructive testing applications to determine the location size and shape of defects - Muhammad Azman Subehi (2019)
Welding is an important aspect of any industry. It helps bind, join and hold two parts together. However due to the nature of the process, there is a possibility that defects such as cracks is introduced to the material. However, it is very expensive to replicate these defects given the cost for time and labour for welding. Thus the author will be looking into 3D Printing technology to see whether it is feasible to replicate the aforementioned defects using metal and non-metal materials. With the availability of Non-Destructive Testing, it is currently one of the conventional ways of detecting these defects. In this report, ultrasonic testing in the form of A-Scan and C-Scan will be used to detect the aforementioned defects in the 3D Printed specimens. In the experiment that is going to be conducted, two specimen will be 3D printed. One specimen will be made out of Aluminium Silicate (AlSi) and the other specimen will be made out of PolyLactic Acid (PLA). Both specimens will be fabricated with defects inside them. After which these specimens are tested with the A-Scan and C-Scan machine to test the viability of using 3D Printing to replicate defects within specimens for structural studies.